2019
DOI: 10.1103/physrevlett.123.237201
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of αRuCl3 in Proximity to Graphene

Abstract: In the pursuit of developing routes to enhance magnetic Kitaev interactions in α-RuCl3, as well as probing doping effects, we investigate the electronic properties of α-RuCl3 in proximity to graphene. We study α-RuCl3/graphene heterostructures via ab initio density functional theory calculations, Wannier projection and non-perturbative exact diagonalization methods. We show that α-RuCl3 becomes strained when placed on graphene and charge transfer occurs between the two layers, making α-RuCl3 (graphene) lightly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 63 publications
12
71
0
Order By: Relevance
“…This value is consistent with previous measurements of the Hall resistance ( n = 2.8 × 10 13 cm –2 ) 8 and is in good agreement with theoretical expectation ( Figure 1 c,d). 27 We note that the agreement between the experimental and model dispersions was improved by assuming that the topmost layer of α-RuCl 3 possesses additional optical conductivity ( Figure S5 ) compared to that of undoped α-RuCl 3 . 28 Hence, our data establish the notion of large interfacial doping and enhanced optical conductivity in α-RuCl 3 as suggested by DFT calculations ( Figure 1 c,d).…”
Section: Quantifying Interfacial Charge Dynamics With Cppsmentioning
confidence: 80%
“…This value is consistent with previous measurements of the Hall resistance ( n = 2.8 × 10 13 cm –2 ) 8 and is in good agreement with theoretical expectation ( Figure 1 c,d). 27 We note that the agreement between the experimental and model dispersions was improved by assuming that the topmost layer of α-RuCl 3 possesses additional optical conductivity ( Figure S5 ) compared to that of undoped α-RuCl 3 . 28 Hence, our data establish the notion of large interfacial doping and enhanced optical conductivity in α-RuCl 3 as suggested by DFT calculations ( Figure 1 c,d).…”
Section: Quantifying Interfacial Charge Dynamics With Cppsmentioning
confidence: 80%
“…The JT physics, even though rarely explored, is universal in spin-orbit Mott insulators and plays an important part when describing the low energy physics such as in Sr 2 IrO 4 and Ca 2 RuO 4 71 . Through the pseudospin-lattice coupling, the JT effect generates new terms or renormalizes the coupling constants in the Hamiltonian 8,71,72 through modifying the wave functions. For instance, the symmetry allowed Γ term is originated from the non-zero trigonal crystal field as shown in Eq.…”
Section: Trigonal Crystal Field Effectmentioning
confidence: 99%
“…It has been proposed that monolayer RuCl 3 on graphene (illustrated in Fig. 3d) would result in a system with enhanced Kitaev type interactions [75,76]. By using ab initio calculations, it was shown that the RuCl 3 becomes strained and doped in this heterostructure.…”
Section: B Experiments Qsl With Anisotropic Interactionsmentioning
confidence: 98%
“…3a) can be potentially adiabatically connected to quantum spin-liquid states realized in α-RuCl 3 (RuCl 3 ) [74,89,[91][92][93], and thus in the following we will focus on this compound. RuCl 3 is a layered Mott insulator with significant spin-orbit interactions that is in the close proximity to the quantum spinliquid ground state [66,74,75]. However, these materials often host complex Hamiltonians having several contributions beyond the Kitaev exchange, including first, second and third neighbor exchange, and symmetric off-diagonal exchange [74,[94][95][96].…”
Section: B Experiments Qsl With Anisotropic Interactionsmentioning
confidence: 99%